2014
DOI: 10.4161/15384047.2014.986997
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin induces cell death of the main molecular myeloma subtypes, particularly the poor prognosis subgroups

Abstract: Multiple myeloma (MM), a plasma cell malignancy, remains incurable despite the development of new therapies. Curcumin anti-tumor effects were previously characterized in multiple myeloma, however only few MM cell lines were included in these studies. Since myeloma is a heterogeneous disease it is important to address the impact of myeloma molecular heterogeneity in curcumin cell death induction. In the present study, a large panel of human myeloma cell lines (HMCLs) (n = 29), representing the main molecular MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“… 11 Furthermore, curcumin-induced cell death was not influenced by myeloma molecular heterogeneity. 12 …”
Section: Discussionmentioning
confidence: 99%
“… 11 Furthermore, curcumin-induced cell death was not influenced by myeloma molecular heterogeneity. 12 …”
Section: Discussionmentioning
confidence: 99%
“…The pleiotropic effects of curcumin can be summarised in the following [6] apoptosis by induction of caspase activity (demethoxycurcumin) [10] Mcl-1 downregulation [12] Radiosensitisation [15] Chemosensitisation [16] Diabetes/metabolic syndrome Improve insulin sensitivity [17] increases the levels of anti inflammatory cytokines like adiponectin [19,20] improved endothelial function [21] decrease in inflammatory cytokines and oxidative stress markers [21] Skin diseases decreases IL-22 levels [23] Osteoarthritis (Curcuma domestica) apoptosis of synovial adherent cells. [30] Neuroprotection Alzheimer disease(in vitro)…”
Section: Curcumin On Depression:-mentioning
confidence: 99%
“…In a study done on HMCL (Human Myeloma cell lines), it was shown that Mcl-1, which is an important protein for myeloma cells to survive in the body, was drastically downregulated in curcumin treated cells [12] .Some subgroups of myeloma cell lines like t(4;14) and t(14;16), which are usually considered as poor prognostic factors were found to be highly sensitive to curcumin [12] .…”
mentioning
confidence: 99%
“…The SNP rs16897930 is located in an intron of PDE10A (phosphodiesterase 10A) and encodes a protein that is important for signal transduction by regulating the intracellular concentration of cyclic nucleotides. The phosphodiesterase encoded by PDE10A gene has recently been shown to be a target of curcumin, a drug that has shown apoptotic effect in myeloma cell lines including those with t(4;14) and t(14;16)(12;13). …”
mentioning
confidence: 99%